Modification of sintered iron properties by Y₂O₃ nanoparticles - Cherednyk, M.I.; Popov, O.Yu.; Chornobuk, S.V.; Totsky, I.M.; Semenko, M.P.; Boshko, O.I.; Tkachuk, V.Ja.; Slobodianyk, Y.V.; Naumenko, S.M.; Makara, V.A. (Functional Materials, 2016)
Influence of Y₂O₃ nanoparticles on sintered iron structure and microhardness is investigated. Ferrite grain growth is shown to be slowed down by the clusters which cause altering the grain shape from needle-like to equiaxial (with lower specific surface). Yttrium oxide particles resulted microhardness increasing to 3.6 GPa at 1 % of second phase content. The fact is explained by retardation of dislocations on disperse particles by the Orowan mechanism.